Towards an agroecology of knowledges: Recognition, cognitive justice and farmers’ autonomy in France - Coolsaet, Brendan (Journal of Rural Studies, 2016)
Most collective agroecological initiatives in Europe today are built around a plurality of knowledge systems. Going beyond the well-documented instrumental goals of this knowledge-plurality, this paper highlights another, perhaps less obvious objective: the pursuit of recognition and cognitive justice. The subordination of alternative farming practices, such as agroecology, to industrial high-input farming leads to the misrecognition of peasant communities. Challenging industrial agriculture hence requires both equality between different forms of doing farming and an active engagement with different ways of knowing farming. Cognitive justice, a concept originating in decolonial thought, encompasses not only the right of different practices to co-exist, but entails an active engagement across their knowledge-systems. Using an example of participatory maize breeding in France, the paper illustrates how peasant movements in Europe organize an ’agroecology of knowledges’, a counter-hegemonic engagement with modern agronomic science, through the recovery and co-production of situational, environment-specific knowledge, and the reskilling of farmers. It aims not only at improving agricultural science, but also at rebuilding collective identities and reclaiming autonomy.
Keywords: Agroecology of knowledges; Autonomy; Cognitive justice; Participatory breeding; Recognition